(-2xy^2)^3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 13:43:57
(-2xy^2)^3(-2xy^2)^3(-2xy^2)^3-8x^3*y^6你好,会有天使爱鬼王:(-2xy²)³=(-2)³×(xy²)³=-8x
(-2xy^2)^3
(-2xy^2)^3
(-2xy^2)^3
-8x^3*y^6
你好,会有天使爱鬼王:
(-2xy²)³
=(-2)³×(xy²)³
=-8x³y^6
3xy-4xy-(-2xy)
3xy-4xy-(-2xy)
(-3xy+2xy)-(4xy+xy)
(-4xy^3)×(-xy)+(-3xy^2)^2
计算:3xy-4xy-(-2xy)要过程
(1)3xy-4xy-(-2xy)
(3xy²)*(-2xy)
3xy-3xy-xy+2yx
2xy.(-3xy)÷(xy)
2xy-xy-(-3xy)=
先去括号,再合并同类项: -3xy+(2xy+3xy-2xy)
[(2xy-3)(2xy+3)+(xy+3)^2]/(-xy)
xy-3xy+2xy-xy
3xy^2*(-2xy)
(X-3xy+4xy-y)-[-2x-2(xy-3/2xy)-y]+6xy的过程
计算:3xy(x²y-xy²+xy)-xy²(2x-xy+2x)
计算:3xy-4xy-(-2xy)3xy-4xy-(-2xy)-1/3ab-1/4a²+1/3a²-(-2/3ab)
已知(x+1)*(x+1)=-Iy-1I,求2(xy-(5xy)*(5xy))-3((xy)*(xy)-xy)